2017
DOI: 10.1093/geront/gnx083
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Antipsychotic Medication Use in Nursing Homes: A Qualitative Study of Nursing Staff Perceptions

Abstract: Nursing home staff recognize the value of reducing antipsychotic medications; however, they also experience multiple barriers to reduction in routine clinical practice. Achievement of further reductions in antipsychotic medication use will require significant additional efforts and adequate clinical personnel to address these barriers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 44 publications
1
42
0
Order By: Relevance
“…In outpatient consultations, psychiatrists were less likely to suggest reduction or discontinuation than service users were to request it [30]. Practitioners in nursing homes felt that antipsychotic reduction could lead to a better quality of life, but were concerned about risk and potential relapse [31,32]. However there is little research directly focusing on the views of mental health professionals in secondary care on antipsychotic reduction and discontinuation (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In outpatient consultations, psychiatrists were less likely to suggest reduction or discontinuation than service users were to request it [30]. Practitioners in nursing homes felt that antipsychotic reduction could lead to a better quality of life, but were concerned about risk and potential relapse [31,32]. However there is little research directly focusing on the views of mental health professionals in secondary care on antipsychotic reduction and discontinuation (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Underuse as well as overuse of psychotropic medication have also been reported in this population (Hanlon et al, 2011). Moreover, a recent study on the use of psychotropic medications in care homes identified potential benefits of antipsychotic medication reduction (Simmons, 2017).…”
Section: Psychotropic Medication Usementioning
confidence: 76%
“…This qualitative study shows limited understanding of what goals of care are and the lack of motivation to initiate conversations with residents and their caregivers. Studies show staff do not know how to lead conversations with residents and their caregivers regarding the risk vs benefits of high‐risk medication and this qualitative study reveals that this extends to conversations about pharmaceutical goals of care. A CCDSS, accompanied with education and training, can guide staff to initiate discussions with the resident and undertake resident assessment of pharmaceutical goals in the care planning.…”
Section: Discussionmentioning
confidence: 89%